The investigaciojn, the technology and the psychology objected, complementary or integrated - Arenas Iparraguirre, Carlos (2009)
This article emerges do the necessity of relocate the relations between science, technological development and the own research. In our country, particularly in the public universities, psychology has oriented its action to the field of technology and the own research. It is ascertained that the transition of the development of scientific psychology has associated to the development of the psychology in the field of professional implementation using for that the own technology of models of intervention, from the clinical, educational or social and organizational field. Nevertheless, it is also recognizable that the production and the generation of systematical knowledge have progressed in a parallel way to the scientific research.